PHARMACOKINETIC OPTIMIZATION AND TOXICITY MITIGATION OF CARDIAC GLYCOSIDES: THERAPEUTIC DRUG MONITORING OF DIGOXIN IN CHRONIC HEART FAILURE WITH ATRIAL FIBRILLATION (World Bulletin of Public Health, 2026)
The integration of cardiac glycosides into contemporary cardiovascular pharmacotherapy demands an extraordinarily precise balance between positive inotropic efficacy and the constant threat of life-threatening proarrhythmic toxicity. This study evaluates the specific clinical, hemodynamic, and electrocardiographic outcomes of utilizing digoxin under strictly controlled pharmacokinetic parameters compared to traditional empirical dosing in a highly vulnerable patient cohort. A prospective clinical analysis was conducted involving 128 adult patients diagnosed with chronic heart failure with reduced ejection fraction and concomitant rapid atrial fibrillation. Subjects were stratified into two clinical pathways: a conventional empirical dosing cohort (n=62) receiving standard maintenance doses based strictly on body weight, and a targeted pharmacokinetic-guided cohort (n=66) where dosing was continuously adjusted via therapeutic drug monitoring and real-time glomerular filtration rate calculations. Clinical data indicate that static, uncalibrated dosing frequently ignores the highly variable volume of distribution and unpredictable renal clearance inherent to this drug class. The targeted cohort demonstrated a 91.0% success rate in achieving optimal serum trough concentrations (0.5–0.9 ng/mL), directly correlating with a rapid reduction in resting ventricular rates from 118 ± 12 bpm to 78 ± 8 bpm without inducing atrioventricular blockade. Conversely, the empirical group exhibited a 24.1% incidence of subclinical and overt digitalis toxicity, driven by unrecognized hypokalemia and transient renal impairment. The dynamics of the observed results suggest that the narrow therapeutic index of digoxin renders historical prescribing habits obsolete. Comprehensive pharmacotherapy must actively integrate rigorous serum concentration tracking, electrolyte stabilization, and continuous dynamic renal assessment to harness the vagomimetic benefits of cardiac glycosides while neutralizing their lethal toxic potential.